Analisis Karakteristik Parkir Terhadap Kebutuhan Ruang Parkir Di Jalan Merdeka Kota Palembang - Ammar Asyraf; Hendrik Jimmyanto; Ani Firda; Aditha Maharani Ratna (Universitas Muhammadiyah Palembang, 2026)
The increasing intensity of commercial and office activities in Palembang City has led to a growing demand for parking spaces, particularly along road segments with mixed land-use functions. Jalan Merdeka was selected as the study location because it experiences high traffic volumes and serves as the administrative center of Palembang City, characterized by a concentration of offices, commercial areas, and traditional markets. This study aims to analyze parking characteristics, including parking volume, parking accumulation, and parking duration, along Jalan Merdeka from the Pasar 26 Ilir segment to the Palembang City Bappenda Office. Data were collected through direct parking surveys conducted on both weekdays and weekends. The survey data were analyzed to identify parking space utilization patterns and to evaluate the conformity between parking demand and existing parking capacity. The results indicate that during weekends, market and culinary areas exhibit higher parking volumes and accumulations, while on weekdays, office areas are dominated by longer parking durations. In general, parking demand on several road segments exceeds the available parking capacity, resulting in intensive use of parking spaces along the study corridor. These findings are expected to serve as a basis for planning and managing parking facilities in urban areas.